Sosialisasi Peningkatan Kinerja Kasir Pada PT Kitita Alami Propertindo - Adinda Putri Aulia; Aep Saefullah; Tetti Nur Intan Rifia; Joned Ceilandra Saksana; Rahman Upe; Moh Tahang; Haria Saputri; Ibah Misbah; M Khairul Umam; Sartika Aini; Adam Samsudin Noor (KREATIF: Jurnal Pengabdian Masyarakat Nusantara, 2021)
PT Kitita Alami Propertindo, Bekasi, faces challenges in managing efficient and accurate cashier transactions, which have an impact on customer satisfaction and daily operations. This activity aims to improve cashier performance through structured training and the use of appropriate technology. The program will be implemented during December 2021. The methods used include theoretical and practical training regarding the use of POS (Point of Sale) systems, time management and customer service. In addition, cashiers are given direct guidance in the field to apply the knowledge gained. Results show significant improvements in transaction efficiency and accuracy, with average transaction times reduced by 20% and error rates reduced by 15%. Customer satisfaction has also increased, as can be seen from surveys showing an increase in satisfaction scores from 75% to 85%. Activity Implications: Improving cashier performance not only improves daily operations but also increases customer trust and satisfaction. Implementation of more efficient POS technology and ongoing training are recommended to ensure continued performance improvements.